TP53 Gain-of-Function and Non–Gain-of-Function Mutations Are Differentially Associated With Sidedness-Dependent Prognosis in Metastatic Colorectal Cancer. Issue 2 (10th January 2022) - Pan, Minggui; Jiang, Chen; Tse, Pam; Achacoso, Ninah; Alexeeff, Stacey; Solorzano, Aleyda V.; Chung, Elaine; Hu, Wenwei; Truong, Thach-Giao; Arora, Amit; Sundaresan, Tilak; Suga, Jennifer Marie; et al.
Abstract : PURPOSE: To examine the association of gain-of-function (GOF) and non–gain-of-function (non-GOF) TP53 mutations with prognosis of metastatic right-sided (RCC) versus left-sided colorectal cancer (LCC). METHODS: This cohort study included patients with metastatic colorectal cancer (CRC) who had next-generation sequencing performed from November 2017 to January 2021. We defined R175H, R248W, R248Q, R249S, R273H, R273L, and R282W as GOF and all other mutp53 as non-GOF. We used Cox regression modeling to examine the association between GOF and non-GOF mutp53 and overall survival (OS), adjusting for age, sex, ethnicity, performance status, Charlson comorbidity index and receipt of chemotherapy. RESULTS: Of total 1, 043 patients, 735 had tumors with mutp53 and 308 had wild-type p53 (wtp53). GOF was associated with worse OS than non-GOF mutp53 only in LCC (hazard ratio [HR] = 1.66 [95% CI, 1.20 to 2.29]), but not in RCC (HR = 0.79 [95% CI, 0.49 to 1.26]). Importantly, RCC was associated with worse OS than LCC only in the subset of patients whose CRC carried non-GOF (HR = 1.76 [95% CI, 1.30 to 2.39]), but not GOF mutp53 (HR = 0.92 [95% CI, 0.55 to 1.53]) or wtp53 (HR = 0.88 [95% CI, 0.60 to 1.28]). These associations were largely unchanged after also adjusting for RAS, BRAF, and PIK3CA mutations, and microsatellite instability-high. CONCLUSION: Poorer survival of patients with metastatic RCC versus LCC appeared to be restricted to the subset with non-GOF mutp53, whereas GOF versus non-GOF mutp53 was associated with poorer survival only among patients with LCC. This approach of collectively classifying mutp53 into GOF and non-GOF provides new insight for prognostic stratification and for understanding the mechanism of sidedness-dependent prognosis. If confirmed, future CRC clinical trials may benefit from incorporating this approach. Abstract :